A rapid and sensitive system for recovery of nucleic acids from Mycobacteria sp. on archived glass slides - A. Talip, Balkis; J. Snelling, William; D. Sleator, Roy; Lowery, Colm; G. Dooley, James S. (BioMed Central, 2018)
The field of diagnostics continues to advance rapidly with a variety of novel approaches, mainly dependent upon high technology platforms. Nonetheless much diagnosis, particularly in developing countries, still relies upon traditional methods such as microscopy. Biological material, particularly nucleic acids, on archived glass slides is a potential source of useful information both for diagnostic and epidemiological purposes. There are significant challenges faced when examining archived samples in order that an adequate amount of amplifiable DNA can be obtained. Herein, we describe a model system to detect low numbers of bacterial cells isolated from glass slides using (laser capture microscopy) LCM coupled with PCR amplification of a suitable target. Mycobacterium smegmatis was used as a model organism to provide a proof of principle for a method to recover bacteria from a stained sample on a glass slide using a laser capture system. Ziehl-Neelsen (ZN) stained cells were excised and catapulted into tubes. Recovered cells were subjected to DNA extraction and pre-amplified with multiple displacement amplification (MDA). This system allowed a minimum of 30 catapulted cells to be detected following a nested real-time PCR assay, using rpoB specific primers. The combination of MDA and nested real-time PCR resulted in a 30-fold increase in sensitivity for the detection of low numbers of cells isolated using LCM. This study highlights the potential of LCM coupled with MDA as a tool to improve the recovery of amplifiable nucleic acids from archived glass slides. The inclusion of the MDA step was essential to enable downstream amplification. This platform should be broadly applicable to a variety of diagnostic applications and we have used it as a proof of principle with a Mycobacterium sp. model system.